How much would low- and middle-income countries benefit from addressing the key risk factors of road traffic injuries?. Issue 1 (2nd January 2020) - Bhalla, Kavi; Mohan, Dinesh; O'Neill, Brian
Abstract: Despite strong advocacy, the UN Decade of Action for Road Safety (2011–2020) is ending with most low- and middle-income countries (LMICs) no closer to the Sustainable Development Goals target of reducing traffic mortality by half. In contrast, most high-income countries (HICs) have seen large benefits in recent decades from large-scale safety interventions. We aimed to assess how much LMICs would benefit from interventions that address six key risk factors related to helmet use, seatbelt use, speed control, drink driving, and vehicle design for safety of occupants and pedestrians. We use a comparative risk assessment framework to estimate mortality and health loss (disability adjusted life years lost, DALYs) that would be averted if these risks were reduced through intervention. We estimate effects for six countries that span all developing regions: China, Colombia, Ethiopia, India, Iran, and Russia. We find relatively large benefits (27% reductions in road traffic deaths and DALYs) from speed control in all countries, and about 5%-20% reductions due to other interventions depending on who is at risk in each country. To achieve larger gains, LMICs would need to move beyond simply learning from HICs and undertake new research to address risk factors particularly relevant to their context.